Louis Malle - Frey, Hugo; Manchester University Press (Manchester, UK : Manchester University Press, 2019)
'This is the first monograph on controversial French director Louis Malle to be published in English. Hugo Frey introduces Malle's work through a lucid analysis of his many masterpieces, including Le Feu Follet, Lacombe Lucien and Au revoir les enfants. He also traces the director's extended period of work in the USA, which resulted in powerful films such as Pretty Baby, Atlantic City USA and My Dinner with André. The book focuses on the most challenging aspects of Malle's oeuvre, his aesthetic vision, his youthful attraction to a form of right-wing pessimism, and his 1970s libertarianism. By rethinking Malle's portrayals of Nazi-occupied France, Frey demonstrates that he is of equal importance to contemporary historians as to film studies. This new appraisal is a nuanced study of an important film-maker, and a critical intervention in the debates which surround Malle's work' --Back cover.
Acknowledgements -- 1. In the eye of the storm -- 2. Aesthetic vision -- 3. Active pessimism and the politics of the 1950s -- 4. Malle's histories -- 5. Primal scenes -- 6. Conclusion -- Filmography -- Select bibliography -- Index.
Made available via: manchesterhive.
Includes bibliographical references, filmography and index.
In English.
Print version record
JSTOR
Keywords: Malle, Louis, -- 1932-1995 -- Criticism and interpretation; Malle, Louis, -- 1932-1995; Motion picture producers and directors -- France; Producteurs et réalisateurs de cinéma -- France; Film, TV and radio; Film scripts and screenplays; PERFORMING ARTS -- Film -- History & Criticism; PERFORMING ARTS / Film / History & Criticism; Motion picture producers and directors; France; The Arts -- Performing arts -- Films, cinema -- Film history, theory & criticism; Electronic books; Criticism, interpretation, etc